Toward multiplex health: integrating complexity, normativity, and Open Science - Qadir, Junaid; Maddah, Diana; Qoronfleh, M. Walid; Senturk, Recep (Frontiers in Psychology, 2025)
Contemporary healthcare remains constrained by models grounded in linear causality, predictive logic, and biomedical reductionism—models that often fail to address the lived, relational, and spiritual dimensions of health, especially under uncertainty. This paper introduces the Multiplex Health (MH) framework as a coherent alternative, rooted in critical complexity theory and multiplex ontology and epistemology. MH advances six core principles: (1) multiplex ontology—viewing humans as multi-layered beings encompassing material, metaphysical, and spiritual domains; (2) multiplex epistemology—integrating empirical, experiential, and interpretive ways of knowing; (3) pluralistic modeling—combining mechanistic, statistical, and semiotic approaches; (4) critical complexity—recognizing health as emergent, open, and irreducible to single models; (5) triangulated science—linking Big Data and Small Data, and balancing prediction with understanding; and (6) comparative multiplex ethics— drawing on Islamic BioFiqh to integrate legal, moral, and spiritual reasoning in health decision-making. By foregrounding the behavioral, ethical, and conceptual dimensions often overlooked in conventional approaches, MH offers a foundational framework for advancing Population Health Management (PHM). A PHM case study focused on mental health illustrates how MH can navigate complexity, enhance relational care, and broaden the scope of well-being beyond reductionist paradigms. MH challenges the dominance of closed, optimization-driven models in precision health and artificial intelligence, instead calling for a “both-and” logic that embraces uncertainty, diversity, and contextual nuance.